2009
DOI: 10.1016/j.hrthm.2009.03.048
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular tachycardia from the healed myocardial infarction scar: Validation of an animal model and utility of gene therapy

Abstract: Life-threatening ventricular arrhythmias generally occur in the setting of structural heart disease. Current clinical options for patients at risk for these rhythm disturbances are limited. We developed a porcine model of inducible ventricular tachycardia originating in the border region of a healed myocardial infarction scar. After validating the model, we assessed gene transfer techniques, focusing on local modification of border zone tissues. We found that gene transfer of the dominant negative KCNH2-G628S … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 33 publications
3
20
0
Order By: Relevance
“…Unlike the reproducibility that we saw in SMVT induction, VF was only a sporadic finding and was not consistently induced every week in any animal. Overall, the pre–gene transfer observations in this study (MI survival, VF and SMVT inducibility) were similar to our previously published experience with the porcine healed MI–VT model (3,10). …”
Section: Resultssupporting
confidence: 90%
“…Unlike the reproducibility that we saw in SMVT induction, VF was only a sporadic finding and was not consistently induced every week in any animal. Overall, the pre–gene transfer observations in this study (MI survival, VF and SMVT inducibility) were similar to our previously published experience with the porcine healed MI–VT model (3,10). …”
Section: Resultssupporting
confidence: 90%
“…In this study, we used a porcine model of MI [34] in which transmural infarction was present in the apical to mid levels. Mean infarct volume was 16% of LV volume with no post-MI variations at 11 days and one month (p = NS).…”
Section: Discussionmentioning
confidence: 99%
“…Also, we did not perform pathologic validation of our model. However, this porcine model of MI has been characterized using high resolution ex vivo CMR [37] and has been reported to exhibit all the morphologic and functional remodeling features of clinical infarctions [34]. There is also extensive published literature on the spatial correlation of infarct and its neighboring regions with delayed enhancement.…”
Section: Discussionmentioning
confidence: 99%
“…This and the rate of inducibility are consistent with Garan et al, 12 who reproduced VT in canines till 6 weeks postinfarct. However, Sasano et al 13 demonstrated an increase (20% week 1 to 90%, week 5) in the rate of inducibility. Contrary to this, Bhandari et al 14 in a clinical study saw a decline in VT inducibility from 15 to 150 days but strong concordance in noninducibility.…”
Section: Vt Inducibilitymentioning
confidence: 96%